Pengaruh Kompetensi SDM dan Peran Audit Intern terhadap Kualitas Laporan Keuangan Pemerintah Daerah dengan Variabel Intervening Sistem Pengendalian Internal Pemerintah (studi empiris pada Pemkab Kebumen) - Syarifudin, Akhmad (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2014)
This research is conducted the Human Resource competency Influence and Role of Internal Audit on the Quality of local Goverment Finacial Report (LKPD) either directly or mediated by SPIP (Government Internal Controling System). Common problems in this study are; 1)The demand in improving LKPD quality, transparency and public accountability. 2). Readiness of personnel competence with the change in SAP (Goverment Accounting Standards). 3). The application of SPIP and, 4). The new role of Internal Audit , it’s not only as the finance controler but also management consultant/SPIP builder. 5)There are someaudit findings that are not detected by internal auditor eiter BPKP or The Inspectorate, but it was found by the BPK (Supreme Audit Agency) later. Research variabels are elaborated operationally in several indicators. Apparatus competence variable is elaborate into five indicators namely; knowledge, skill, motives, traits, and self concept. Variable of Intrnal Audits role is elaborated into three indicators namely; The role of supervisor, coaching/ consulting and revieww of finncial report.Varianle of Government Internal Controling System is elaborated into five indicators namely; Internal control, risk assesment, controling activity, information and communication, and monitoring. The variable of local government financial report quality is elaborated into fou indicators namely;relevan, reliable, it can be compared, and easy to understand. The population in this research are all regional works unit of Kebumen regency that are involved in the process of local Government financial reporting. The data is taken by questionnaires which is ditributed to respondents. The variable in this study is independent variable Comptency (X1), Independncy (X2), while the dependent variable s the Government’s Intenal Controling System (Y1) and Quality of Local Government Financial Report/LKPD (Y2). Data were analyzed using “Amos 18.0. The reseach result show that ; 1) HR competency has unsignificant positive effect on the quality of LKPD. 2) The role of InternalAudit has unsignificant positife effect on the quality of LKPD. 3) SPIP has siginificant positifve effect on the quality LKPD. 4) HR competency has significant positive effect to SPIP. 5) The role of Internal Audit has significant positive effect on SPIP. 6) HR competency which is mediated by SPIP has unsignificant positive effect on the quality LKPD. 7) The role of Internal Audit which is mediated SPIP has unsignificant positive effect on the quality of LKPD.